Rapid Aortic Enlargement Requiring Surgery in Patients with Chronic Type B Aortic Dissection - Hata, Mitsumasa; Akiyama, Kenji; Wakui, Shinji; Takasaka, Ayako; Shiono, Motomi (The Thoracic and Cardiovascular Surgeon, 2012)
We report the relationship between rapid aortic enlargement of chronic type B aortic dissection and sleep disorder due to anxiety after Tohoku disaster. Five patients underwent surgical procedures due to rapid aortic enlargement after the earthquake disaster. They reported that their morning blood pressure increased to approximately 190 mm Hg after the disaster. They were troubled with severe insomnia due to anxiety about the continuing aftershocks. In primary care for patients with mental stress after a big disaster, it is important to keep a careful monitoring of blood pressure besides assessment of anxiety and sleep.
Keywords: aortic dissection; sleep disorder; Tohoku disaster